Regulations Of The Capital Market And Social Responsibility - Manurung, Suntika Dewi; Siregar, Emiel Salim; Siregar, M. Reno Ramadhana; Panjaitan, Lathifah Wulandari; Tanjung, Silvia Mahdalena; Adly, Adly; Putri, Galu Raka (Peneliti.net, 2024)
Every state consistently endeavors to foster the progress, well-being, and prosperity of its citizens. One approach frequently adopted by states involves actively attracting foreign investments. The Investment Law outlines three fundamental principles. Firstly, it emphasizes the rule of law, encompassing key tenets such as equal treatment for both domestic and foreign investments, transparency, and accountability. Secondly, it assures protection against nationalization and includes mechanisms for dispute resolution. Thirdly, it advocates for the simplification of investment procedures and licensing services through a centralized one-stop mechanism. It is crucial to recognize that economic development is not solely the responsibility of the government and its populace; investors also play a pivotal role. The establishment of social responsibility frameworks for investors serves as a legal foundation, guiding them in their commitment to environmental stewardship. By implementing social responsibility initiatives, companies and investors contribute indirectly to enhancing the well-being of local communities in a given region.